ABOUT THE PROBLEM OF ENVIRONMENTAL-CAUSED HEALTH DISORDERS - V. S. Rukavishnikov; N. V. Efimova (Acta Biomedica Scientifica, 2012)
The article reviews the main problem, of environmental hygiene and medical ecology — the absence of unity of methodological approaches to the detection of environmental health, disorders (EHD).